Increased Subjective Distaste and Altered Insula Activity to Umami Tastant in Patients with Bulimia Nervosa - Setsu, Rikukage; Hirano, Yoshiyuki; Tokunaga, Miki; Takahashi, Toru; Numata, Noriko; Matsumoto, Koji; Masuda, Yoshitada; Matsuzawa, Daisuke; Iyo, Masaomi; Shimizu, Eiji; Nakazato, Michiko (Frontiers in Psychiatry, 2017)
The aim of this study was to examine differences in brain neural activation in response to monosodium glutamate (MSG), the representative component of umami, between patients with bulimia nervosa (BN) and healthy women (HW) controls. We analyzed brain activity after ingestion of a MSG solution using functional magnetic resonance imaging (fMRI) in a group of women with BN (n=18) and a group of HW participants (n=18). Both groups also provided a subjective assessment of the MSG solution via a numerical rating scale. The BN group subjectively rated the MSG solution lower in pleasantness and liking than the control group, although no difference in subjective intensity was noted. The fMRI results demonstrated greater activation of the right insula in the BN group versus the control group. Compared to the HW controls, the BN patients demonstrated both altered taste perception-related brain activity and more negative hedonic scores in response to MSG stimuli. Different hedonic evaluation, expressed as the relative low pleasing taste of umami tastant and associated with altered insula function, may explain disturbed eating behaviors, including the imbalance in food choices, in BN patients.